Dynamic Event-Triggered Sliding Mode Control of Markov Jump Delayed System with Partially Known Transition Probabilities - Jie Lu; Yang Jia; Xiang Cai; Jinnan Luo; Jiachen Li (Mathematics)
This paper investigates the dynamic event-triggered (ET) sliding mode control (SMC) of Markov jump delayed systems (MJDSs) with partially known transition probabilities. Firstly, a dynamic ET scheme is introduced for the Markov SMC system, and the effect of time delays is considered. In addition, the Razumikhin condition is used to deal with the time delay. Moreover, in the case of a Markov jump system with partially known transition probabilities, using the vertex method, weak infinitesimal generator, and Dynkin’s formula, the finite-time boundness (FTB) problem of a class of ET SMC systems with stochastic delay is studied. Finally, a numerical example is given to illustrate the viability of our results.